Study to Assess the Effectiveness of Planned Health Teaching Programme on Knowledge Regarding Prevention of Mental Illness among the Caretaker of Patients Admitted in a Tertiary Health Center of City - Salve, Priyanka; Kengale, Manisha; Koshti, Maheshwari; Chopade, Manoj; Jagdhane, Shradha; Gaikwad, Sneha (Innovational: Journal of Nursing and Healthcare, 2024)
Background: A quasi-experimental research was to assess the effectiveness of planned health teaching program on knowledge regarding prevention of mental illness among the caretaker of patient’s admitted in tertiary health center of city. Objectives: The objective of the study was to assess the effectiveness of planned health teaching program on knowledge regarding prevention of mental illness among the caretaker of patients admitted in tertiary health center of city and to find the association of study finding with selected demographic variables. Methods: A consecutive sampling technique was used to select the sample. In the present study, sample consisted of 74 caretakers of patients admitted in tertiary health center of the city which is Sassoon General Hospital, Pune. The content validity was determined by the experts. The reliability of tool was done by Karl Pearson’s test-retest method. Pearson’s correlation coefficient was found to be 0.90. The final data collection was scheduled from April 16, 2019, to April 28, 2019. Results: We applied paired t-test to assess the effectiveness of planned health teaching program on knowledge regarding prevention of mental illness among participants. Average pre-test score was 12.27 which increased to 15.87 in post-test. t-value for this test was 14.97 with 0.05% level of significance, which is greater than tabulated value, thus null hypothesis was rejected. Chi-square test was used to assess the association of study findings with selected demographic variables. The Chi-square value for education was 11.85 with 0.05% level of significance, which is greater than tabulated value; hence, it was a significant association with the study findings. This was also evident that the knowledge of the participant improved significantly after planned health teaching program. Conclusion: The study concludes that the knowledge regarding prevention of mental illness among the caretaker of patients admitted in tertiary health center of city, also concludes that the effectiveness of planned health teaching program on knowledge regarding prevention of mental illness among the caretaker of patients admitted in tertiary health center of city, and, furthermore, concludes the association of study finding with selected demographic variables.